Deposition and Photocatalytic Activity of Ag:V2O5 Thin Films. (14th April 2016) - González-Zavala, F.; Escobar-Alarcón, L.; Solís-Casados, D. A.; Arroyo Rebollar, D.; Basurto, R.; Haro-Poniatowski, E.
ABSTRACT: In this work, the deposition and photocatalytic response of V2 O5 thin films modified with different amounts of Ag (Ag:V2 O5 ) is reported. Films were deposited on glass and silicon substrates (100), using the pulsed laser deposition (PLD) technique. A high purity vanadium target, with a different number of silver pellets attached on it were used. Thin films were characterized by energy dispersive spectroscopy (EDS) to determine the elemental chemical composition; structural changes due to the addition of Ag were monitored by Raman spectroscopy; Optical microscopy was used to observe the surface morphology and UV-Vis spectroscopy was employed to determine optical properties. Photocatalytic response of the prepared films was studied through the degradation of a malachite green solution using a solar irradiation source.